Contactless and Spatially Resolved Determination of Current−Voltage Curves in Perovskite Solar Cells via Photoluminescence. Issue 8 (8th August 2021) - Bui, Anh Dinh; Mahmud, Md Arafat; Mozaffari, Naeimeh; Basnet, Rabin; Duong, The; Bartholazzi, Gabriel; Le, Tien T.; Truong, Thien N.; Tebyetekerwa, Mike; Wibowo, Ary; Weber, Klaus J.; White, Thomas P.; et al.
Abstract : Imaging In article number 2100348, Anh Dinh Bui, Daniel Macdonald, Hieu T. Nguyen, and co‐workers report a fast, non‐invasive, camera‐based method to image pseudo current density ‐ voltage curves of various perovskite‐based structures from partially finished to finished cells with micron‐scale spatial resolution. This approach is useful to resolve the inhomogeneity of implied open‐circuit voltage and maximum fill factor across the devices, and their evolution during degradation.